Nutrition and Helicobacter pylori: Host Diet and Nutritional Immunity Influence Bacterial Virulence and Disease Outcome - Kathryn P. Haley; Jennifer A. Gaddy (Gastroenterology Research and Practice)
Helicobacter pylori colonizes the stomachs of greater than 50% of the world’s human population making it arguably one of the most successful bacterial pathogens. Chronic H. pylori colonization results in gastritis in nearly all patients; however in a subset of people, persistent infection with H. pylori is associated with an increased risk for more severe disease outcomes including B-cell lymphoma of mucosal-associated lymphoid tissue (MALT lymphoma) and invasive adenocarcinoma. Research aimed at elucidating determinants that mediate disease progression has revealed genetic differences in both humans and H. pylori which increase the risk for developing gastric cancer. Furthermore, host diet and nutrition status have been shown to influence H. pylori-associated disease outcomes. In this review we will discuss how H. pylori is able to create a replicative niche within the hostile host environment by subverting and modifying the host-generated immune response as well as successfully competing for limited nutrients such as transition metals by deploying an arsenal of metal acquisition proteins and virulence factors. Lastly, we will discuss how micronutrient availability or alterations in the gastric microbiome may exacerbate negative disease outcomes associated with H. pylori colonization.